The Theory of Business Profits - Marshall, Alfred (Quarterly Journal of Economics, 1887)
Journal Article The Theory of Business Profits Get access Alfred Marshall Alfred Marshall Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 4, July 1887, Pages 477–481, https://doi.org/10.2307/1879342 Published: 01 July 1887